The Role of Satintelkam Improvement to Prevent Labor and Company Social Conflicts in the Jurisdiction of the Pasuruan Police (Indonesian Journal of Police Studies, 2024)
The number of demonstrations carried out by labor groups in the Pasuruan District Police jurisdiction during 2021-2023 resulted in losses of both property and casualties, so it is necessary to take preventive measures by taking into account aspects of protection, human rights, legal norms and a sense of justice for the community. Therefore, the researcher examines the role of Satintelkam's mobilization in preventing social conflicts between laborers and companies at Pasuruan District Police. The qualitative approach method was used in this research by conducting descriptive analysis. Data collection was carried out using observation, interview, and document study techniques. The theories in this research are POAC management theory, SWOT theory, accompanied by the concept of role, the basic concept of intelligence gathering, and the concept of MOPI. This research shows that the role of Satintelkam in preventing labor and company social conflicts is optimal but there are still things that need to be improved or developed in carrying out early detection and early prevention.
Keywords: Kata kunci: Satintelkam, Penggalangan, Konflik Sosial Buruh